Comparison of different models for the estimation of genetic parameters of body weight traits in Moghani sheep - Hossein-Zadeh, Navid Ghavi; Ardalan, Mehrnaz (MTT Agrifood Research Finland, 2010)
Genetic parameters for birth weight (BW), 3-month weight (3MW), 6-month weight (6MW), 9-month weight (9MW) and yearling weight (YW) in Iranian Moghani sheep were estimated using restricted maximum likelihood procedure of MTDFREML program. The data and pedigree information used in this research were collected at the Breeding station of Moghani sheep (Ardebil province, Iran) during 1987 2005. Six different animal models were fitted, differentiated by including or excluding maternal effects, with and without covariance between maternal and direct genetic effects. The estimates for direct heritability ranged from 0.31 to 0.54, 0.21 to 0.34, 0.13 to 0.25, 0.11 to 0.22 and 0.10 to 0.17 for BW, 3MW, 6MW, 9MW and YW, respectively. The estimates were substantially higher when maternal effects, either genetic or environmental, were ignored in the model. The results of this study show that full models with maternal genetic and environmental effects gave the most accurate estimates for body weight traits in Moghani sheep.
Keywords: heritability; animal model; growth traits; maternal effect; meat sheep